Ionothermal synthesis of octahedral lanthanoid coordination networks exhibiting slow magnetization relaxation and efficient photoluminescence. Issue 4 (4th January 2021) - Yang, Ting-Hai; Wang, Shu-Fan; Lin, Chen-Lan; Wang, Xin; Zhu, Binglong; Wu, Dayu
Abstract : An ionothermal reaction of lanthanoid salts with tetraethyl- p -xylenediphosphonate (tepxdp) in ionic liquids, such as choline chloride and malonic acid, resulted in the formation of three novel lanthanoid–organic coordination networks with the formula [Ln(H2 pxdp)1.5 ] n . Abstract : An ionothermal reaction of lanthanoid salts with tetraethyl- p -xylenediphosphonate (tepxdp) in ionic liquids, such as choline chloride and malonic acid, resulted in the formation of three novel lanthanoid–organic coordination networks with the formula [Ln(H2 pxdp)1.5 ] n Ln = Tb (1 ), Dy (2 ) and Ho(3 ) and H4 pxdp = p -xylenediphosphonic acid. The structures, photoluminescence and magnetic properties of the three compounds were investigated in detail. Single crystal X-ray diffraction analysis revealed that the three compounds are isostructural and the Ln 3+ ions show an unusual six-coordinate environment with the LnO6 octahedron. In these compounds, each PO3 C tetrahedron is corner-shared with two LnO6 octahedra and each LnO6 octahedron is corner-shared with six PO3 C tetrahedra, thus forming an inorganic layer in the crystallographic ab plane. The inorganic layers are further connected by a phenyl group, leading to a three-dimensional framework. Compound 1 exhibits the strong and characteristic emission of Tb III with an impressive quantum yield of 46.2%. Detailed magnetic analysis demonstrated that compound 2 displays a slow magnetic relaxation of magnetization with multiple relaxation mechanisms. The anisotropic energy barrier and the pre-exponential factor τ 0 are 51.2 K and 3.9 × 10 −7 s, respectively, in the presence of a direct-current field of 500 Oe. This work demonstrates a successful strategy to isolate octahedrally coordinated lanthanoid complexes through ionothermal synthesis to exhibit the single-ion-magnet-like behaviour and photoluminescence properties.